2019
DOI: 10.4197/med.26-1.5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Complications of Hemoglobinopathies in Western Saudi Arabia and the Need for Specialized Care Centers

Abstract: In the absence of specialized care centers for hemoglobinopathies in Saudi Arabia, there are insufficient data on prevalence of clinical complications in this population. This is a retrospective record review about the clinical complications associated with hemoglobinopathies at King Abdulaziz University Hospital, for patients followed between January 1st 2010 through June 30th 2016. A total of 349 patients were included, with a mean age of 25.45 years, including 266 with sickle cell disease and 80 with thalas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…A previous study (Sewwandi Karunaratna et al, 2017) in SriLankan patients with β-thalassemia, was reported that patients' mean of serum ferritin concentration was significantly higher than control. Furthermore, the findings of this study was agreed with previous studies conducted in Saudi Arabia (Badawi et al, 2019), Pakistan (Riaz et al, 2011), and India (Mishra & Tiwari, 2013) and Egypt (Mathematics, 2016) The results of study were shown highly statistical significance increases of serum ALT and AST in the thalassemia major group 24.5 ± 22.5 and 40.5 ± 41.7, when compared with control group (15.1 ± 9.7 and 22 ± 8.9); P value were 0.026 and 0.017, respectively. These results were in agreement with a study conducted by (Kasarala & Tillmann, 2016), who proved that several biochemical markers, including AST, ALT, and albumin, are widely known to reflect hepatic function.…”
Section: Comparison Between Control and Thalassemia Majorsupporting
confidence: 92%
“…A previous study (Sewwandi Karunaratna et al, 2017) in SriLankan patients with β-thalassemia, was reported that patients' mean of serum ferritin concentration was significantly higher than control. Furthermore, the findings of this study was agreed with previous studies conducted in Saudi Arabia (Badawi et al, 2019), Pakistan (Riaz et al, 2011), and India (Mishra & Tiwari, 2013) and Egypt (Mathematics, 2016) The results of study were shown highly statistical significance increases of serum ALT and AST in the thalassemia major group 24.5 ± 22.5 and 40.5 ± 41.7, when compared with control group (15.1 ± 9.7 and 22 ± 8.9); P value were 0.026 and 0.017, respectively. These results were in agreement with a study conducted by (Kasarala & Tillmann, 2016), who proved that several biochemical markers, including AST, ALT, and albumin, are widely known to reflect hepatic function.…”
Section: Comparison Between Control and Thalassemia Majorsupporting
confidence: 92%
“… 3 Individuals affected with inherited hemoglobinopathies are at high risk of anaemia, infections, pain, and can suffer from cardiac, endocrine and pulmonary complications leading to frequent need for hospitalisation. 4 , 5 Furthermore, the need to receive frequent blood transfusions may subject affected individuals to a higher risk of acquiring blood-borne disorders, such as hepatitis c. 6 …”
Section: Introductionmentioning
confidence: 99%